Analisis Pengaruh Rasio Keuangan Risk Based Capital dan Early Warning System Terhadap Harga Saham (Studi Empiris pada Perusahaan Asuransi yang Listing di BEI tahun 2008 - 2012) - Hapsari, Tania; Basri, Yesi Mutia; ', Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aimed to examine the effect of Financial Risk Based CapitalRatio and Early Warning System consisting of; Claims Expense Ratio, Liquidity Ratio, Agents Balance to Surplus Ratio and Growth Rate on Stock Price Premiums on insurance companies listed on the Stock Exchange in 2008-2012. The population in this research is the insurance company listed on the Indonesia Stock Exchange in the year 2008-2012. There are 11 insurance companies listed on the Indonesia Stock Exchange in the year 2008-2012. Based on purposive sampling method was obtained 9 Insurance companies as samples in this study. This research was conducted with the multiple linear regression method, the processing of data using SPSS for Windows version 20. The result of this research showed that liquidity ratio significantly affect the stock price on the insurance companies listed on the Stock Exchange 2008-2012 period. But the risk-based ratio, the ratio of claims expenses, agents balance to surplus ratio and the ratio of premium growth did not significantly affect the stock price on the insurance companies listed on the Stock Exchange 2008-2012 period. As for the test results showed that the coefficient of determination value of Adjusted R2 of the model research was 0.763. The condition means that the independent variables are risk-based capital ratio, the ratio of claims expenses, liquidity ratio, the ratio of agents to balance the surplus and premium growth rate of 76% has effect on the dependent variable is the stock price on the insurance companies listed on the Stock Exchange in 2008 -2012. As for the rest, 24% are influenced by variables or other factors not examined in this research.Keywords: Financial Risk Based Capital Ratios, Financial Ratios EarlyWarning System,Claims Expense Ratio, Liquidity Ratio, AgentsBalance to Surplus Ratio, Premium Growth Ratio, Stock Price.